2015
DOI: 10.1002/btpr.2052
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of active recombinant interleukin‐12/eGFP fusion protein in stably‐transfected DF1 chicken cells

Abstract: The adjuvant activity of chicken interleukin-12 (chIL-12) protein has been described as similar to that of mammalian IL-12. Recombinant chIL-12 can be produced using several methods, but chIL-12 production in eukaryotic cells is lower than that in prokaryotic cells. Stimulating compounds, such as dimethyl sulfoxide (DMSO), can be added to animal cell cultures to overcome this drawback. In this study, we constructed a cell line, DF1/chIL-12 which stably expressed a fusion protein, chIL-12 and enhanced green flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…To identify the fusion protein production, both the culture supernatant and cell lysate were examined by western‐blotting. The results indicated that fusion protein in the culture supernatant was not detected (data not shown), similar to those of our previous studies, in which rchIL‐12 or IL‐18 synthesized by rFPV/chIL‐12 or −18 10 or chIL‐12/eGFP fusion protein was evident as a cell‐associated protein. Conversely, a major protein band with an estimated size of 55 kDa, which is consistent with the expected size of the fusion protein, was detected in the cell lysate of DF1/chIL‐18a, because this protein was recognized by antibodies against the FLAG peptide (Figure C, lane 2), eGFP (Figure D, lane 2), and the echIL‐18 (Figure E, lane 2) .…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…To identify the fusion protein production, both the culture supernatant and cell lysate were examined by western‐blotting. The results indicated that fusion protein in the culture supernatant was not detected (data not shown), similar to those of our previous studies, in which rchIL‐12 or IL‐18 synthesized by rFPV/chIL‐12 or −18 10 or chIL‐12/eGFP fusion protein was evident as a cell‐associated protein. Conversely, a major protein band with an estimated size of 55 kDa, which is consistent with the expected size of the fusion protein, was detected in the cell lysate of DF1/chIL‐18a, because this protein was recognized by antibodies against the FLAG peptide (Figure C, lane 2), eGFP (Figure D, lane 2), and the echIL‐18 (Figure E, lane 2) .…”
Section: Resultssupporting
confidence: 91%
“…Such protein production was lower, in comparison to the aforementioned results. This could be because the fusion protein, chIL‐18/eGFP, rather than a single chIL‐18 was synthesized in this study, rendering possible the less effective expression of such a large protein, as previously described …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations